THE EXTENT TO WHICH SOCIAL AUDIT CONTRIBUTES TO SOCIAL RESPONSIBILITY AND SUSTAINABLE DEVELOPMENT - Mohammed Farhan flayylh Alabbassi, Dr.Fatima Saleh Mehdi AlGharban (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Social audit and social responsibility have become the focus of governments and economic units to address challenges, risks and crises that require community awareness and commitment. The research aims to know the contributions of social audit in economic units and its importance and the vital role of achieving social responsibility and sustainability and the treatment of some of the social problems, and to find opportunities by economic units and society in order to raise the level of the barrier sought for individuals if the problem of research includes weak planning of strategic social audit, and social responsibility especially their importance to the life of the individual and society was used \ reports of the Federal Financial Supervisory Office to achieve the objectives of research and it was reached that social audit has an active and important role in achieving social responsibility and sustainable development and that the most important Research recommends it is to encourage and encourage economic units to recognize the importance of social auditing, social responsibility and sustainable development.